Building the foundation for equitable and inclusive research: Seed grant programs to facilitate development of diverse CBPR community–academic research partnerships. Issue 1 (24th November 2023) - Coombe, Chris M.; Simbeni, Sophia; Neal, Aaron; Allen, Alex J.; Gray, Carol; Guzman, J. Ricardo; Lichtenstein, Richard L.; Marsh, Erica E.; Piechowski, Patricia; Reyes, Angela G.; Rowe, Zachary; Weinert, Julia; et al.
Abstract: Introduction: The effectiveness of community-based participatory research (CBPR) partnerships to address health inequities is well documented. CBPR integrates knowledge and perspectives of diverse communities throughout the research process, following principles that emphasize trust, power sharing, co-learning, and mutual benefits. However, institutions and funders seldom provide the time and resources needed for the critical stage of equitable partnership formation and development. Methods: Since 2011, the Detroit Urban Research Center, collaborating with other entities, has promoted the development of new community–academic research partnerships through two grant programs that combine seed funding with capacity building support from community and academic instructors/mentors experienced in CBPR. Process and outcomes were evaluated using mixed methods. Results: From 2011 to 2021, 50 partnerships received grants ranging from 2, 500 to 30, 000, totaling 605, 000. Outcomes included equitable partnership infrastructure and processes, innovative pilot research, translation of findings to interventions and policy change, dissemination to multiple audiences, new proposals and projects, and sustained community–academic research partnerships. All partnerships continued beyond the program; over half secured additional funding. Conclusions: Keys to success included participation as community–academic teams, dedicated time for partnership/relationship development, workshops to develop equity-based skills, relationships, and projects, expert community–academic instructor guidance, and connection to additional resources. Findings demonstrate that small amounts of seed funding for newly forming community–academic partnerships, paired with capacity building support, can provide essential time and resources needed to develop diverse, inclusive, equity-focused CBPR partnerships. Building such support into funding initiatives and through academic institutions can enhance impact and sustainability of translational research toward advancing health equity.